SJECH M. DJAMIL DJAMBEK PENGKRITIK TAREKAT YANG MODERAT DI MINANGKABAU - Tarihoran, Adlan Sanur (Alhurriyah, 2011)
Sjech. M. Djamil known as a reformer scholars in various fields including in education, theology and tarekat (Islamic religious order) in Minangkabau. This paper will research Sjech M. Djamil Djambek contact with tarekat and his criticism of the tarekat. Tarekat Syatthariyah and Naqsabandiyah are a growing tarekat early in the Minang area. Then, the tarekats have be criticized by Ulama in Minangkabau. Sjech M. Djamil Djambek learned from tarekat. He also member of tarekat. He is accommodative figure and give constructive critique. His critic is without disregard silaturrahim (personal relationship). His critique is reason without hurt feeling. So, all parties are welcome to Sjeh M Djamil. His style is moderate and quite moderate and step forward to his time.